Copper, zinc and selenium imbalance in Moroccan haemodialysis patients and its correlation to lipid peroxidation - Eljaoudi, Rachid; Errasfa, Mourad; Benyahia, Mohammed; Bahadi, Abdelali; Cherrah, Yahia; Ibrahimi, Azeddine; Elkabbaj, Driss (International Journal of Research in Medical Sciences, 2017)
Background: Haemodialysis patients are at risk of developing trace elements imbalance and lipid peroxidation. The present study was aimed to assess plasma levels of copper (Cu), zinc (Zn), selenium (Se) and malondialdehyde (MDA) of haemodialysis patients and to investigate the possible effect of haemodialysis on these trace elements and MDA imbalance. Methods: Blood samples of fifty hemodialysis patients and forty healthy controls subjects were analyzed for determination of hemoglobin, albumin, creatinine, urea and high-sensitivity C-reactive protein (hs-CRP). Cu, Zn and Se were determined in plasma (before and after hemodialysis) and erythrocytes and MDA in plasma before and after hemodialysis. Results: The study showed that, plasma Zn and Se concentrations were lower in haemodialysis patients compared to that of healthy controls, while plasma Cu, MDA and Cu/Zn ratio were higher. Plasma Cu/Zn ratios were positively correlated to MDA and weakly correlated to hs-CRP levels whereas plasma Se concentrations were inversely correlated to MDA. In addition, MDA levels increased after haemodialysis session. Conclusions: Based on the results of the present study regarding the imbalance of trace elements in haemodialysis patients, it seems reasonable to periodically assess the trace elements status and consider possible correctional therapy in case of deficiency.